2022
DOI: 10.1097/j.pain.0000000000002718
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the trajectory curve of long-term musculoskeletal post-COVID pain symptoms in hospitalized COVID-19 survivors: a multicenter study

Abstract: Female sex, previous history of pain symptoms, pain symptoms at onset, and days at hospital were factors associated with highly prevalent musculoskeletal post-COVID pain 1 year after hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…D’Souza et al observed that the most common type of post-COVID pain described by patients themselves on social media resembles a musculoskeletal/nociceptive pain phenotype [ 26 ]. In fact, a large cohort study reported that post-COVID pain in previously hospitalized COVID-19 survivors was of musculoskeletal origin in 45% of subjects at eight [ 27 ] and twelve [ 28 ] months after hospitalization. These authors stated that 30% of COVID-19 survivors with post-COVID pain reported the presence of symptoms solely in localized body areas (e.g., neck, shoulder, elbow, knee, or hip), another 30% exhibited pain in the extremities, and 20% in the spine, whereas the remaining 20% had widespread symptoms [ 27 , 28 ]; however, these authors did not differentiate between pain from muscular or articular origin.…”
Section: Phenotyping Post-covid Painmentioning
confidence: 99%
See 2 more Smart Citations
“…D’Souza et al observed that the most common type of post-COVID pain described by patients themselves on social media resembles a musculoskeletal/nociceptive pain phenotype [ 26 ]. In fact, a large cohort study reported that post-COVID pain in previously hospitalized COVID-19 survivors was of musculoskeletal origin in 45% of subjects at eight [ 27 ] and twelve [ 28 ] months after hospitalization. These authors stated that 30% of COVID-19 survivors with post-COVID pain reported the presence of symptoms solely in localized body areas (e.g., neck, shoulder, elbow, knee, or hip), another 30% exhibited pain in the extremities, and 20% in the spine, whereas the remaining 20% had widespread symptoms [ 27 , 28 ]; however, these authors did not differentiate between pain from muscular or articular origin.…”
Section: Phenotyping Post-covid Painmentioning
confidence: 99%
“…A primary feature of nociplastic pain is the presence of regional or widespread pain symptoms [ 19 ]. The presence of regional, including widespread, pain can reach up to 70% of COVID-19 survivors [ 27 , 28 ]. Generalized pain symptoms, combined with central sensitization-associated symptoms (e.g., higher CSI scores) could help identify nociplastic pain in the IASP-established criteria.…”
Section: Phenotyping Post-covid Painmentioning
confidence: 99%
See 1 more Smart Citation
“…In the face of a high-severity pandemic (such as COVID-19), keeping patients alive is of absolute importance, and pain assessment may not be a priority. However, if patients' pain is undertreated and underestimated, it can become chronic and strongly interfere with their post-COVID lives (Kemp et al 2020 ; Fernández-de-las-Peñas et al 2021a , 2023 ). Although studies report days of hospitalization as a risk factor for the development of post-COVID-19 musculoskeletal pain symptoms (Kemp et al 2019 ; Fernández-de-las-Peñas et al 2021b , a ), the chronic pain and persistent poor health after COVID-19 may not necessarily be associated with respiratory complications, initial disease severity, or the need for hospital care (Logue et al 2021 ; Townsend et al 2021 ).…”
Section: Covid-19 Symptoms and Their Relation With Chronic Painmentioning
confidence: 99%
“…In this sense, a subset of patients who faced non-severe COVID-19 disease has reported persistent painful symptoms, which included fatigue/muscle weakness (70.6%), trouble with mobility (7%), headaches (68%), and myalgias (55%) (Graham et al 2021 ; Nehme et al 2021 ; Moghimi et al 2021 ). Moreover, it has been shown that painful symptoms might persist for 7–12 months, ranging from one to five complaints (Huang et al 2021b ; Nehme et al 2021 ; Fernández-de-las-Peñas et al 2023 ). Some symptoms, such as myalgia, arthralgia, and fatigue, appear early in the infection and persist.…”
Section: Covid-19 Symptoms and Their Relation With Chronic Painmentioning
confidence: 99%